Exploring Local Wisdom: Ethnoscientific Study of Durian Tempoyak-Making in Indragiri Hilir as a Source of Science Learning - Lestari, Ina; Ikhsan, Muhammad (Jurnal Pijar Mipa, 2025)
Local wisdom-based learning is one of the innovative approaches in science education that enhances the relevance of scientific knowledge to everyday life. One form of local wisdom that can be studied from an ethnoscientific perspective is the production of durian tempoyak in Indragiri Hilir, Riau. The fermentation process of durian tempoyak involves scientific concepts in biology and chemistry, such as microorganism activity, fermentation reactions, and changes in food's physical and chemical properties. However, research on integrating local wisdom into science education remains very limited. This study aims to analyze local wisdom in the production of durian tempoyak from a scientific perspective. Data were collected through interviews with informants selected using the snowball sampling method. Data analysis was conducted using the Miles and Huberman qualitative approach. The research findings indicate that the Malay community continues to preserve the tradition of making durian tempoyak. The production process includes preparing materials and tools, fermentation stages, and its benefits in science learning. In conclusion, exploring ethnoscience in durian tempoyak production provides an opportunity to link science with local culture, particularly in biotechnology. Integrating local wisdom into science education will enhance students’ appreciation of culture and develop 21st-century skills.